The effect of ergonomics in dentistry on the occurrence of pain in the cervical neck region of the spine - Płocki, Jędrzej; Pikuła, Dominik; Banaś, Joanna; Kotela, Andrzej (Medical Studies/Studia Medyczne, 2015)
Introduction: The problem of health risks resulting from the performance of the occupation of a dentist concerns, among other things, the cervical region of the spine. Due to the position assumed at work, this part of the spine is overloaded, and the degree of this overload depends, among other things, on the technique used by a dentist, the ergonomic conditions, patient adaptation skills, and cooperation with an assistant or assistants. Aim of the research : The objective of the study was to obtain an answer to the research questions posed: whether dentists possess knowledge concerning the principles of ergonomics; is there any relationship between the period of employment and cervical spine pain, age, technique of work, duration of performing work during the week, and pain in the neck region; and if dentists attach importance to the prophylaxis of musculoskeletal disorders. Material and methods : The study covered 52 dentists – 33 females (63.5%) and 19 males (36.5%), and was conducted using an anonymous questionnaire designed by the authors, the Visual Analogue Scale (VAS), a modified pain assessment questionnaire according to Laitinen, and methods of descriptive statistics (Pearson’s χ 2 test for independence). Results : Physicians possess knowledge concerning the ergonomics of work. In addition, more than 60% of respondents possess modern, electrically adjustable equipment, and the technique of work depends on the age of the dentist. There is a relationship between cervical spine pain and the duration of performance of the occupation (p = 0.01122). According to dentists (48.1%), pain in the neck region of the spine is caused by long-lasting maintenance of a static position of the body, and kinesitherapeutic exercises alleviate these complaints in 23.1% of respondents. Conclusions : Despite the use the principles of ergonomics at work, dentists are exposed to the occurrence of pain in the neck region of the spine.